Exploring the calcium isotope signature of Arctica islandica as an environmental proxy using laboratory- and field-cultured specimens - Hippler, D.; Witbaard, R.; van Aken, H.M.; Buhl, D.; Immenhauser, A. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
The calcium-isotope composition (delta Ca-44/40) of the aragonitic bivalve Arctica islandica grown in laboratory and field cultures was investigated in terms of environmental and biological controls to explore its potential as a palaeoceanographic proxy. While we found no significant effect of salinity on Ca-isotope fractionation, the relationship between Ca-44/Ca-40 ratios of A. islandica and temperature was best explained by a generalised additive model, which describes the temperature versus Ca-isotope relationship as a nonlinear, second-degree polynomial with an optimum temperature of 15 degrees C. Since Ca-44/Ca-40 ratios clearly increase with increasing temperature up to 15 degrees C, the temperature versus Ca-isotope relation can be approximated through a linear fit up to 15 degrees C. The slope of this linear temperature dependent Ca-isotope fractionation resembles previous calibrations of inorganic and biogenic aragonites, providing insights into fractionation processes during bivalve biomineralization. Our findings suggest that the observed biologically-induced Ca-isotope fractionation occurs when Ca is transported from seawater to the site of mineralization, most likely during the passage through the epithelial mantle. The observed evidence for strong vital effects indicates limited use of Ca isotopes in A. islandica as a temperature proxy.